Three-dimensional hierarchical self-supported NiCo2O4/carbon nanotube core–shell networks as high performance supercapacitor electrodes1. Issue 11 (7th February 2015) - Li, Xiaocheng; Sun, Wei; Wang, Liqun; Qi, Yongdong; Guo, Tieming; Zhao, Xinhong; Yan, Xingbin
<x xml:space="preserve">Abstract</x> A three-dimensional hierarchical self-supported NiCo2O4/carbon nanotube core–shell network structure shows good supercapacitive performance in both three-electrode and two-electrode cell systems.